Axinite, a Borosilicate with Extensive Fe-Mn Substitutions at the Scale of Monocrystal Revealed by Micro-XRF Imaging and In Situ Analysis: An Example from the Type Locality at Oisans (France) - Michel Cathelineau; Olivier Gerbeaud; Chantal Peiffert (Crystals)
Axinite crystals from the type locality (Oisans, French Alps) are considered among the more remarkable specimens known for their quality (lustre, colour, size, and purity) and crystalline forms. However, they have been the subject of only a few in-depth studies. This lack of knowledge provided the opportunity for a systematic survey of axinites from Saint-Christophe-en-Oisans, where crystals appear to cover an extensive range of Fe-Mn substitution from an Fe-rich (axinite-Fe) to a Mn-rich field (axinite-Mn) in a same crystal, with compositional variations much more significant than initially described. An in-depth characterisation of the chemical zonation of the crystals using EPMA, Raman spectroscopy, X-ray micro-fluorescence, and LA-ICP-MS was carried out on the crystals showing the most significant variability. The micro-XRF method appeared extremely useful for describing spatial variations in chemical composition at the centimetre scale and preparing other in situ methods. Fe(Mg)-Mn substitution covers a large range but the Mn-enriched growth zones are relatively thin and localised at the periphery of crystals. In addition, chemical zonations highlighted in this study also reveal contrasted incorporation of trace elements as a function of the Fe/Mn ratio (in particular, Be, HREE, Sc, Ga, In, and Co), indicating changes in fluid chemistry during the crystal growth.